PENGARUH KUALITAS PRODUK DAN HARGA TERHADAP KEPUTUSAN PEMBELIAN STUDI KASUS CAFE REZA KABUPATEN SIDENRENG RAPPANG - Herman, Nahdatul Putri; Kadir, Abdul; Basri, Jumriah (Universitas Ichsan Sidenreng Rappang, 2025)
This research aims to determine the influence of product quality on purchase decisions at Café Reza in Sidenreng Rappang Regency, as well as to analyze the impact of price on purchase decisions at the same café. The method used in this study is a quantitative approach by processing questionnaire results to identify the factors affecting purchase decisions. Questionnaires were distributed to respondents who were customers of Café Reza and had made a purchase. The data analysis methods used in this study include validity and reliability tests, classical assumption tests, hypothesis testing, and the coefficient of determination test, all processed using IBM SPSS. The t-test results show that the product quality variable has a partially positive influence on purchase decisions, with a significance value of 0.000 < 0.05. Likewise, the price variable also has a partial influence on purchase decisions at Café Reza, with a significance value of 0.005 < 0.05. Simultaneously, both variables show a significance value of 0.000, indicating that both have a significant influence on purchase decisions at Café Reza. The coefficient of determination analysis shows that 43.7% of the variation in purchase decisions can be explained by the product quality and price variables.